2017
DOI: 10.1039/c7dt00326a
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid derivative rare-earth dinuclear complexes and one-dimensional architectures: synthesis, characterization and magnetic properties

Abstract: Discrete and extended architectures based on the association of lanthanide ions with two derivatives of cinnamic acid (2-methoxycinnamic acid and 3-methoxycinnamic acid) have been synthesized and characterized by IR spectroscopy, elemental analyses, X-ray diffraction and magnetic measurements. The use of the 2-methoxycinnamic ligand enables the synthesis of a series of dinuclear complexes (Ce (1), Nd (2), Gd (3), Dy (4)), while the presence of 3-methoxycinnamic acid induces the formation of one-dimensional coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…in the presence of sodium hydroxide in a DMF/water mixture allows for the formation of colorless crystals after re-crystallization in DMSO. The crystals that usually form rapidly are a one-dimensional coordination polymer, which we previously reported [30]. Remarkably, we have found that the kinetics of crystallization constitutes an important parameter that can be used to provide a further degree of control.…”
Section: Synthesis and Crystal Structurementioning
confidence: 85%
See 3 more Smart Citations
“…in the presence of sodium hydroxide in a DMF/water mixture allows for the formation of colorless crystals after re-crystallization in DMSO. The crystals that usually form rapidly are a one-dimensional coordination polymer, which we previously reported [30]. Remarkably, we have found that the kinetics of crystallization constitutes an important parameter that can be used to provide a further degree of control.…”
Section: Synthesis and Crystal Structurementioning
confidence: 85%
“…This therefore explains the need to use a DC field to reduce this relaxation. The comparison with the previously reported dinuclear dysprosium-based complex involving the 2-methoxycinnamic acid derivative, as well as with the 1-D coordination polymer based on the 3-methoxycinnamic acid ligand [30] clearly sheds light on the role of the coordination environment and packing arrangement over the slow relaxation of the magnetization. While two relaxation processes have been evidenced in the dinuclear complex incorporating the 2-methoxycinnamate, the Orbach process was found negligible in contrast to Raman and direct processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from their excellent magnetic properties, most Ln-CPs also display characteristic sharp and narrow luminescence emissions originating from f-f transitions of the Ln 3+ ions, featuring excellent colour purity, long fluorescence lifetimes and high quantum yields (Roy et al, 2014;Xu et al, 2017;Zhang et al, 2017). Owing to the prominent optical and magnetic properties of Ln-CPs, it is of great importance and an enormous challenge to build dual optical-magneto materials based on lanthanide ions (Li et al, 2015(Li et al, , 2017a which have potential applications in luminescent sensing, magnetic resonance imaging (MRI), cryogenic magnetic refrigeration, high-density information storage and quantum computations (Khalfaoui et al, 2017;Li et al, 2015;Liu et al, 2014;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%